Estudo das Influências de Trocas de Mensagens Assíncronas nos Mecanismos que Implementam a Atomicidade Local - Silveira de Brito, Maria Alice (Cadernos do IME - Série Informática, 2013)
We describe in this paper the issues to be risen if we include the asynchronous message passing on the concurrency control and recovery mechanisms based on serial dependency relation. These mechanisms take into accounting the objects are shared by pessimistic and optimistic transactions. The mechanism can’t use the results and return arguments in the serial dependency relation under a pessimistic one-phase locking transaction, thus, the concurrency chances are reduced. The optimistic transactions execute without synchronization, relying on commit-time validation to ensure serializability, thus, the asynchronous mode is don’t care at run-time. The behavior of pessimistic two-phase locking transactions in object was preserved. These results confirm the chance to include asynchronous message passing in atomic object implementation.